2013
DOI: 10.1111/jog.12224
|View full text |Cite
|
Sign up to set email alerts
|

Amnioinfusion before 26 weeks' gestation for severe fetal growth restriction with oligohydramnios: Preliminary pilot study

Abstract: In cases of extremely severe FGR before 26 WG with oligohydramnios and circulatory failure, amnioinfusion might be a promising, innovative tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…All hypercoiled cords were detected by ultrasound examination before birth, and median UCI was 0.76 (range 0.71-0.93). FD occurred in six cases (cases [9][10][11][12][13][14]. In addition to the early gestational age, the estimated body weight was very small (296, 417, 339 and 322 g) in four cases (cases 9, 10, 12 and 14, respectively).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…All hypercoiled cords were detected by ultrasound examination before birth, and median UCI was 0.76 (range 0.71-0.93). FD occurred in six cases (cases [9][10][11][12][13][14]. In addition to the early gestational age, the estimated body weight was very small (296, 417, 339 and 322 g) in four cases (cases 9, 10, 12 and 14, respectively).…”
Section: Resultsmentioning
confidence: 97%
“…Takahashi et al reported improvement of abnormal UA and DV Doppler by AI when umbilical cord problems were present. 13 A previous study suggested the efficacy of AI for avoiding umbilical cord compression and increasing umbilical blood flow. In the present study, a hypercoiled cord and decreased amniotic fluid were detected in all cases of temporary DV-RAV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, early-onset fetal growth restriction that shows umbilical venous fluctuation and reverse ductus venosus flow, which were observed in this case, is the strongest predictive factor for intrauterine fetal death [9]. Second, almost one-half of the reported cases of early-onset fetal growth restriction were complicated with severe oligohydramnios and destined to die [10]. We believe that in the present case the tadalafil therapy contributed to the improved intrauterine environment and to the extension of the pregnancy to 32 week’s gestation, and finally to the uncomplicated post-delivery course.…”
Section: Discussionmentioning
confidence: 99%